Comparative Study of Influenza Virus and Parainfluenza 3 Virus as Causative Agents of Upper Respiratory System in Thi-Qar Province - Al Ghazi, Abeer; Al Ghazi, Basim (University of Thi-Qar Journal of Science, 2022)
The current study is targeted for detection of the some important respiratory pathogen viruses which responsible for respiratory tract infections, Influenza A virus (IAV) and human Parainfluenza viruses (HPIVs) are considered of the causes of respiratory diseases. The current study included the examination of 150 nasal swab samples from the age of one year to the age of 70 years. The collected specimens were kept in viral transport media (VTM). RNA were extracted.The results revealed from this study are summarized in the follows: out of 150 patients suffering from respiratory tract infection only 20(13.3%) were encountered with the H1N1 virus, 21(14.0%) were HPIV3 .Co-infection of number of viruses appeared in 33(22.0%) patient. The sample are categorized into sex groups were H1N1viruses male 12(8.00%) higher than female 8(5.30%). HPIV3 male 11(7.30%) higher female 10(6.70%).The distribution of H1N1virus based on age groups ,and it represents the highest percentage were 4(2.70%) less than 7 years, 3(2.00%) (57-63)years and 4(2.70%)(64-70)years.The distribution of HPIV3 based on age group, and represents the highest percentage were 4(2.70%)(57-63)years, 4(2.70%)(64-70)years. H1N1virus infections in the December, January, February and March months was higher than the April, HPIV3 infection in the March and April months were higher than the December, January and February months. The main clinical features caused by H1N1, rhinorrhea ,fever and cough were reported as the highest frequently,15(75.0%), 10(50.0%), 9(45.0%) respectively ,the other signs were dyspnea 7(35.0%), sneezing 5(25.0%). HPIV3, rhinorrhea was reported as the highest frequently 16(76.2%), the other signs were sneezing 5(23.8%), cough and fever 4(19.0%)